2016
DOI: 10.1155/2016/1295329
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies in HCC: Radiation Modalities

Abstract: Patients with hepatocellular carcinoma (HCC) comply with an advanced disease and are not eligible for radical therapy. In this distressed scenario new treatment options hold great promise; among them transarterial chemoembolization (TACE) and transarterial metabolic radiotherapy (TAMR) have shown efficacy in terms of both tumor shrinking and survival. External radiation therapy (RTx) by using novel three-dimensional conformal radiotherapy has also been used for HCC patients with encouraging results while its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 91 publications
0
19
0
Order By: Relevance
“…been made in its etiology and treatment research, the prognosis of HCC remains poor (Bimonte et al, 2016;Gallicchio et al, 2016;Hamed et al, 2013;Nishida & Kudo, 2013;Sereni, Rodgers, Kirby, & Goykhman, 2017).…”
mentioning
confidence: 99%
“…been made in its etiology and treatment research, the prognosis of HCC remains poor (Bimonte et al, 2016;Gallicchio et al, 2016;Hamed et al, 2013;Nishida & Kudo, 2013;Sereni, Rodgers, Kirby, & Goykhman, 2017).…”
mentioning
confidence: 99%
“…However, one relevant study pointed out that advanced patients were not suitable for surgical treatment (46) . Radiation therapy, which used to be a palliative option for HCC treatment, has now been proven to be effective for selected advanced HCC patients (47,48) . Therefore, our study revealed that active radiotherapy or chemotherapy could effectively improve the survival of these patients when surgical treatment is no longer suitable.…”
Section: Discussionmentioning
confidence: 99%
“…LP-CDDP was diluted to 10,000-fold with distilled water, and the concentration of platinum was measured using an automatic flameless atomic absorption spectrophotometer (FAAS) (Model AA-6700; Shimadzu, kyoto, Japan) (26). Our previous studies demonstrated that, among the BNC-LP complexes prepared at 70˚C and pH 3.0, the highest yield of BNCs was obtained at a BNC:LP ratio of 1:20 [molar ratio of BNC (as particle):LP (as lipids) = 1:1.6x10 4 or 1:1.6x10 5 , respectively] (21). To produce the BNC-LP-CDDP complex, LP-CDDP was incubated in Britton-Robinson buffer (0.1 M H 3 BO 3 , 0.1 M CH 3 COOH, 0.1 M H 3 PO 4 and 0.5 M NaOH; pH 3.0) at 70˚C for 5 min, mixed with BNC, and then kept at 70˚C for 60 min with gentle stirring.…”
Section: Methodsmentioning
confidence: 99%
“…Radiotherapy is one of the most effective tools in the clinical treatment of many types of solid tumors; however, its use for HCC has been limited due to the intrinsic tolerance of the liver and the development of radiation-induced liver disease (4,5). As an increase in the radiation dose may lead to severe damage to normal tissues around the tumor and could potentially result in wound complications and transformation of tumor to radioresistant ones (6,7), this cannot serve as an option for enhancing the response of cancers to radiation therapy.…”
Section: Introductionmentioning
confidence: 99%